ANALYSIS BUSINESS STRATEGY HOUSING DEVELOPMENT OF MILLENIAL GENERATION - Amalia Ivada; Amie Kusumawardhani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The advance of the highly competitive housing development industry demands housing development companies to do innovation in their housing products. One of the innovations that housing developers can do is to start targeting the millennial generation as a market for their products. The great number of millennials who have already worked and have got married makes them to be the potential buyers to a larger property market. The business strategy analysis was carried out through external environmental analysis utilizing PESTEL analysis and Porter analysis, and internal environmental analysis utilizing business function analysis and strategy formulation with SWOT analysis. This qualitative study used a case study approach. The data were collected by using in-depth interviews with the strategic parties of PT. Kanzu Permai Abadi. The results of this research show that PT. Kanzu Permai Abadi has considered the internal and external aspects of the company in formulating the housing business strategies for the millennial generation. The business strategies by PT. Kanzu Permai Abadi could be used to assess its position well in the housing development industry which is starting to target the millennial generation for its housing products and will not be easily defeated by its competitors. Keywords: Business Strategy, Housing Developer, Millennial Generation.